Closed-form Method for Multi-stage Axial Flux Permanent Magnet Machine: Design and Analysis. Issue 7 (21st April 2017) - Kim, Ju Hyung; Sarlioglu, Bulent
Abstract: Designing an axial flux permanent magnet machine is complex and computationally intensive. This paper proposes a new closed-form method for concurrent design and analysis of a multi-stage axial flux permanent magnet machine. The method will provide a simpler modeling solution to machine designers. By calculating magnetic and electric properties, the design space of an axial flux permanent magnet is created for initial design. This paper demonstrates the feasibility of the new closed-form method by showing that the results obtained from the proposed method correlate with the finite element analysis results. The design space is also evaluated and analyzed by taking into account various parameters, including copper losses, permanent magnet density, phase voltages, and torque waveform. Finally, a multi-objective analysis is performed to compare two different designs of an axial flux permanent magnet machine. The proposed method also provides a useful guide for the initial design state.